Developing, validating, and comparing an analytical method to simultaneously detect z-drugs in urine samples using the QuEChERS approach with both liquid chromatography and gas chromatography-tandem mass spectrometry - Varsha Chauhan; Manu Sharma; Abhishek Tiwari; Varsha Tiwari; Manish Kumar; Ajay Sharma; Arya Lakshmi Marisetti; Ashok Kumar; Abdulsalam Alhalmi; Omar M. Noman; Ahmad Alahdab (Elsevier, 2024)
Detecting z-drugs, a sedative-hypnotic medication, is also misused for criminal activities. Therefore, the analysis of urine samples is crucial for clinical and forensic purposes. We conducted a study where we developed, validated, and compared an analytical method for simultaneously detecting z-drugs in urine samples. Our approach uses the QuEChERS method for sample preparation, combined with liquid chromatography (LC) and gas chromatography (GC) coupled with tandem mass spectrometry (MS/MS). We optimized the QuEChERS method to effectively extract z-drugs from urine samples while minimizing matrix effects and achieving high recovery rates. After extraction, we split the samples into two parts for analysis using LC-MS/MS and GC-MS/MS. We validated our methods, and the results showed good linearity over a broad concentration range (1-200 ng/mL) for each z-drug. The limits of detection and quantification were within clinically relevant ranges, ensuring sensitivity for detecting z-drugs in urine samples. We compared the two chromatographic techniques by analyzing a set of urine samples spiked with known concentrations of z-drugs using both LC-MS/MS and GC-MS/MS methods and then applied to the real samples. The results were statistically analyzed to assess any significant differences in accuracy and precision above 95 %, and both methods offered reliable and consistent results with the samples as well. In conclusion, our analytical method coupled with both LC-MS/MS and GC-MS/MS using the QuEChERS approach provides a comprehensive and robust solution for the simultaneous detection of z-drugs in urine samples. The choice between the two chromatographic techniques can be based on the specific z-drugs of interest and the required analytical performance. This method holds promise for applications in clinical toxicology, forensic analysis, and monitoring z-drug usage.